SOSIALISASI PENCAPAIAN KELUARGA SAKINAH MELALUI PEMBERDAYAAN EKONOMI DI DESA SOOKO KECAMATAN SOOKO - Ghozali, Ghozali; Novita, Mega Darmi; Setyaasih, Setyaasih; Agustina, Ratna (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Various problems in the household prove that realizing a harmonious family requires the involvement of several parties. Cooperation between parents, the Religious Affairs Office (KUA), and the government is necessary in forming a harmonious, loving, and compassionate family. Community service as a form of the Tri Dharma of Higher Education is correlated with the duties of the District Religious Affairs Office (KUA), namely, providing solutions to marital problems. The purpose of this counseling is to reduce the number of divorces and early marriages in the community, especially in Sooko Village, which are caused by various aspects, including economic factors. Therefore, intensive cooperation between the community and government institutions is needed to realize a harmonious family, especially by strengthening the economy, education, and culture. In the field of economic empowerment, the involvement of the regional government and the East Java provincial government is needed to support capital and job training.